Comparing the Efficacy of Professional Athlete-Led Online Instruction and Traditional Coaching for Developing Technical Competencies in Novice Sepak Takraw Players: A 12-Week Randomised Controlled Study - Zulkifli Zulkifli; Raffly Henjilito; Yudanto Yudanto; Jet Longakit; Sm Farooque; Vlad Adrian Geanta; Oleksii Kozin (Здоров’я, спорт, реабілітація)
Background and purpose This study aimed to compare the efficacy of professional athlete-led online instruction with traditional in-person coaching for developing technical competencies in novice sepak takraw players, addressing critical knowledge gaps in digital sports instruction and motor skill development. Material and methods A 12-week randomized controlled study was conducted with 60 participants (40 males, 20 females) aged 14-17 years, divided into experimental (online coaching) and control (in-person coaching) groups. Participants underwent comprehensive pre-intervention testing and were assessed using multiple performance metrics, including service accuracy, spike execution, ball control, and game situation performance. The study employed advanced technological tools such as high-speed cameras, force plates, and motion analysis software to evaluate skill development. Results The experimental group demonstrated significantly greater improvements across most technical skills. Notably, service accuracy improved by 38.67 points compared to 16.76 points in the control group, with statistically significant differences (p<0.01). Spike execution showed substantial enhancements, with the experimental group improving jump height from 27.27 cm to 44.70 cm. While ball control improvements were similar between groups, the online instruction group exhibited more consistent skill development. Game situation performance showed marginal differences, with the experimental group achieving a 33.4% improvement compared to 29.8% in the control group. Conclusions Professional athlete-led online instruction proves to be a highly effective alternative to traditional in-person coaching for developing technical skills in sepak takraw. The study challenges conventional assumptions about motor skill learning, highlighting the potential of digital coaching platforms. While online instruction demonstrates remarkable effectiveness, a hybrid approach may offer optimal skill development, particularly for complex tactical aspects of the sport.